Avaliação da longevidade de vacas da raça Nelore por diferentes critérios utilizando análise de sobrevivência - Ramos, Salvador Boccaletti [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Stayability is economically importante in the beef cattle industry. The longer the cow ramains in the herd, the greater are the chances it will pay for its costs and generate revenue. This study had two objectives: first, evaluate the variable age of cow at last calving (ALC) as a measurement of stayability considering diferent censoring criteria; second, to estimate genetic parameters for the same variable considering the diferent censoring criteria. Records of 22313 Nellore cows, from 13 farms were used in this study. The explanatory variables considered were age at first calving, number of calvings, season and year of birth and farm. Three censoring criteria were chosen: 16, 26 and 36 months of age. Survival analysis techniques were used to evaluate the variable and to estimate survival and risk curves. The variance of the ALC was studied considering the effect of each explanatory variable. The Kaplan-Meier method was used to estimate the cows’survival curves. The Cox proportional hazards model was used to estimate the hazard of the cow being culled. The breeding values and heritability of the hazard of being culled were estimated by a proportional hazards Weibull model. The Spearman correlation test was used to study the rank of the animals considering the three censoring criteria. The greater the censoring criterion addopted, the greater was the number of cows with complete records. The estimated survival curves and hazard functions differ among each other (P<0.05). The stayability estimated considering the 16 months of age criterion was the greater when compared with the other censoring criteria. The heritability estimates for the 16, 26 and 36 months criteria were 0.1020, 0.1002 and 0.0871, respectively. The Spearman correlation estimates for the 16 and 26, 16 and36 and 26 and 36 months of censoring criteria were -0.2124, 0.1348 and 0.1211, respectively (P>0.05). A big part of the ...

A habilidade de permanência da vaca no rebanho é economicamente importante em gado de corte. Quanto mais tempo a vaca permanecer no rebanho, maiores serão as chances da vaca pagar seus custos de recria e gerar lucro ao produtor. Este trabalho teve dois objetivos: primeiro, avaliar a variável idade da vaca ao último parto (IVUP) como medida de habilidade de permanência da vaca no rebanho em diferentes critérios de censura; segundo, estimar parâmetros genéticos para a mesma para cada um dos diferentes critérios de censura considerados. Registros de 22312 vacas da raça Nelore provenientes de 13 fazendas foram utilizados neste estudo. As variáveis explanatórias utilizadas foram idade ao primeiro parto, número de partos, estação e ano de nascimento e fazenda. Três critérios de censura foram escolhidos: 16, 26 e 36 meses de idade. Metodologias de análise de sobrevivência foram utilizadas para a análise dos dados e estimação dos parâmetros das curvas de sobrevivência e risco. A variância de IVUP foi estudada considerando o efeito de cada variável explanatória proposta para os três critérios de censura. A metodologia dos estimadores de Kaplan-Meier foi empregada para estimar a probabilidade da vaca permanecer no rebanho. O modelo de riscos proporcionais de Cox foi utilizado para estimar o risco da vaca deixar o rebanho. Os valores genéticos dos animais e a herdabilidade do risco da vaca deixar o rebanho foram estimados por modelo de riscos proporcionais de Weibull. A análise da classificação dos reprodutores com base no valor genético foi realizada por meio do teste de correlação de Spearman. Quanto maior o valor do critério de censura adotado, maior foi o número de vacas com informações completas incluídas na análise. Há diferenças significativas (P<0,05) entre as funções de sobrevivência e risco dos três critérios adotados. A habilidade de permanência da ...
Keywords: Bovino; Nelore (Zebu); Longevidade; Idade; Análise de sobrevivência (Biometria); Longevity